1990
DOI: 10.1093/schbul/16.2.331
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences of Young Adults With Schizophrenic Disorders in Community Care

Abstract: Gender differences were studied in the lives of 122 young adults (mean age = 23.11 years) with schizophrenia or schizophrenia-related disorders who are participants in a long-term study of progressive community care. Across the first 2 years, males who required hospitalization showed a trend toward greater recidivism and spent more time in institutions than women who required hospitalization. Women spent more time in inpatient medical settings for nonpsychiatric reasons. In community living domains, significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 30 publications
5
78
0
3
Order By: Relevance
“…We found that in the total sample of patients with schizophrenia, men have a higher probability of being admitted while there are no differences in the number of admitted patients and in the length of hospitalisations. Similar results have been described previously 18,19 .…”
Section: Discussionsupporting
confidence: 93%
“…We found that in the total sample of patients with schizophrenia, men have a higher probability of being admitted while there are no differences in the number of admitted patients and in the length of hospitalisations. Similar results have been described previously 18,19 .…”
Section: Discussionsupporting
confidence: 93%
“…The most important difference was found in the independence life area, which is the one that refers to aspects of occupational functioning. Most of the studies that have assessed differences in social functioning in patients with schizophrenia regarding gender have also found a better functioning in women, including those assessing functioning with sociodemographic data 18,19 and those using specific scales as the Disability Assessment Scale (DAS-sv) 20 . In the same line of evidence, Usall 21 found significant differences between men and women in occupational functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Ainsi, l'augmentation du répertoire d'habiletés qu'ont les patients pour composer avec les stresseurs est un des aspects essentiels de la réadaptation psychiatrique. Plusieurs études ont démontré que les répertoires d'habiletés varient en fonction du sexe, du diagnostic et du degré de chronicité des patients (Bellack et al, 1989;Childers et Harding, 1990;Test et al, 1990). …”
Section: Mmêêmêêêimêmmmmmmmêêmammêêmêiêêêiêêmmmrunclassified
“…Les autres items concernant la cuisson des aliments, l'épicerie et l'entreposage des aliments n'ont pu être évalués pour la majorité des participants, ceux-ci étant hospitalisés et n'ayant pas l'occasion d'exercer ces habiletés. Soulignons en outre que les différences significatives obtenues entre les différents groupes de personnes vont dans le sens des travaux de recherche antérieurs, qui ont démontré que les femmes possèdent un répertoire d'habiletés plus vaste que les hommes (Childers et Harding, 1990), que les personnes diagnostiquées comme schizophrènes ont moins d'habiletés que les autres groupes diagnostiqués (Bellack et al, 1989;Test et al, 1990 et que les personnes hospitalisées à long terme possèdent moins d'habiletés pour mener une vie autonome.…”
Section: Analyse Factorielle Exploratoireunclassified